Head posture control under perturbed conditions in progressive supranuclear palsy patients - Lippi, Vittorio; Maurer, Christoph; Haverkamp, Christian; Kammermeier, Stefan (Frontiers in Systems Neuroscience, 2025)
IntroductionIn neurodegenerative brain diseases like Progressive Supranuclear Palsy (PSP), clinical studies underscore the crucial role of head motion deficits. Similarly, advanced stage Idiopathic Parkinson’s disease (IPD) is known to display significantly altered posture control and balance patterns involving the head segment.MethodsThis study investigates the relative differences in head control during a perturbed upright stance paradigm between patients affected by PSP and IPD, compared to healthy control subjects using dynamic system modeling. The resulting neural model underlines how PSP primarily affects head control, whereas IPD primarily affects the control of the whole body’s center of mass. A neck control model, based on the hypothesis of modular posture control, is proposed to emulate the PSP data in particular.ResultsA larger passive stiffness was observed for both groups of patients, with eyes closed, suggesting that the head moves together with the trunk. With eyes open, the active proportional gain KP is relatively larger in all cases, indicating that the head is directed closer to the vertical by the visual contribution. Since this was held for all investigated groups, findings support the notion of intact visual contribution to posture control among PSP and IPD despite the impaired supranuclear eye guidance among PSP.DiscussionThe proposed neural model’s characteristics will aid in future patient data analysis, disease progression monitoring, and possible modulation of disease-specific features through therapeutic intervention. For engineering and robotics implementations, uses for strengthened resilience of head stabilization are discussed.